Ghosts : death's double and the phenomena of theatre - Rayner, Alice (University of Minnesota Press, 2006)
Alice Rayner examines theatre as a memorial practice that is haunted by the presence of loss, looking at how aspects of stagecraft turn familiar elements into something uncanny. Citing examples from the works of Shakespeare, Beckett, and Suzan-Lori Parks as well as the films Vertigo, Gaslight, and The Sixth Sense, Rayner describes time as it is employed by theatre with multiple facets of presence, duration, and passage.